Case Report: A Novel De Novo Missense Mutation of the GRIA2 Gene in a Chinese Case of Neurodevelopmental Disorder With Language Impairment - Zhou, Bingbo; Zhang, Chuan; Zheng, Lei; Wang, Zhiqiang; Chen, Xue; Feng, Xuan; Zhang, Qinghua; Hao, Shengju; Wei, Liwan; Gu, Weiyue; Hui, Ling (Frontiers in Genetics, 2021)
Introducton: Neurodevelopmental disorders with language impairment and behavioral abnormalities (NEDLIB) are a disease caused by heterozygous variants in the GRIA2 gene, which manifests as impaired mental development or developmental delay, behavioral abnormalities including autistic characteristics, and language disorders. Currently, only a few mutations in the GRIA2 gene have been discovered. Methods: A GRIA2 variation was detected in a patient by whole exome sequencing and the site was validated by Sanger sequencing from the family. Results: We report a Chinese case of NEDLIB in a girl with language impairment and developmental delay through whole-exome sequencing (WES). Genetic analysis showed that there was a de novo missense mutation c.1934T>G (p.Leu645Arg) in GRIA2 gene (NM_001083619.1), which has never been reported before. Conclusions: Our case shows the potential diagnostic role of WES in NEDLIB, expands the GRIA2 gene mutation spectrum, and further deepen the understanding of NEDLIB. Deepening the study of the genetic and clinical heterogeneity, treatment and prognosis of the disease is still our future challenge and focus.